A state-of-the-art review on producing engineered biochar from shellfish waste and its application in aquaculture wastewater treatment. (February 2022) - Wan Mahari, Wan Adibah; Waiho, Khor; Azwar, Elfina; Fazhan, Hanafiah; Peng, Wanxi; Ishak, Sairatul Dahlianis; Tabatabaei, Meisam; Yek, Peter Nai Yuh; Almomani, Fares; Aghbashlo, Mortaza; Lam, Su Shiung
Abstract: Global production of shellfish aquaculture is steadily increasing owing to the growing market demands for shellfish. The intensification of shellfish aquaculture to maximize production rate has led to increased generation of aquaculture waste streams, particularly the effluents and shellfish wastes. If not effectively managed, these wastes could pose serious threats to human health and the ecosystem while compromising the overall sustainability of the industry. The present work comprehensively reviews the source, composition, and environmental implications of shellfish wastes and aquaculture wastewater. Moreover, recent advancements in the valorization of shellfish wastes into value-added biochar via emerging thermochemical and modification techniques are scrutinized. The utilization of the produced biochar in removing emerging pollutants from aquaculture wastewater is also discussed. It was revealed that shellfish waste-derived biochar exhibits relatively higher adsorption capacities (300–1500 mg/g) compared to lignocellulose biochar (<200 mg/g). The shellfish waste-derived biochar can be effectively employed for the removal of various contaminants such as antibiotics, heavy metals, and excessive nutrients from aquaculture wastewater. Finally, future research priorities and challenges faced to improve the sustainability of the shellfish aquaculture industry to effectively support global food security are elaborated. This review envisages that future studies should focus on the biorefinery concept to extract more useful compounds (e.g., carotenoid, chitin) from shellfish wastes for promoting environmental-friendly aquaculture. Graphical abstract: Image 1 Highlights: Shellfish aquaculture increases shellfish waste and aquaculture wastewater. Emerging valorization of shellfish waste, the concerns, and disputes are reviewed. Emphasis is on conversion of shellfish into engineered biochar. Emerging waste and pollutant from aquaculture wastewater are reviewed. Applications of engineered biochar to treat aquaculture wastewater are discussed.